Pemberian Nutrisi pada Penderita Kanker Paru - Aulia Salsabila; Indra Buana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Lung cancer is all malignant diseases in the lungs. In Indonesia in 2020, it was ranked third with 34,783 cases. The nutritional problem faced by lung cancer patients is the difficulty of receiving food. As a result of the presence of cancer in the body and the effects of treatment therapy, cancer patients experience various nutritional problems that if not overcome immediately can worsen their health conditions. Experts state that cancer patients need nutritional screening to detect nutritional disorders, as well as weight loss (BB) and body mass index (BMI) since the patient is diagnosed with cancer. Balanced nutrition can inhibit the likelihood of further weight loss and infection. Although the cure rate of cancer patients is still very low, with the right nutritional therapy and a supportive environment, it is hoped that it can support the success of lung cancer patient therapy.